2013
DOI: 10.1007/978-3-642-23380-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Effects of Ionizing Radiation

Abstract: Pancreatic cancer is associated with a high mortality rate, owing to de novo and acquired drug resistance, thereby leading to highly invasive and metastatic pancreatic cancer cells. Therefore, targeting pancreatic cancer stem cells (CSCs) may be a novel therapeutic strategy for the treatment of pancreatic cancer. Here, we combined a DNA methylation inhibitor (5-aza-2'-deoxycytidine; 5-aza-dC) and ionizing radiation (IR) to improve anti-cancer effects by inhibiting growth and proliferation and promoting apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 207 publications
0
4
0
Order By: Relevance
“…As explained in the text, the sex-specific bystander effect that was reported by Koturbash et al [39,143] was observed together with DNA methylation changes. Studies have also shown that epigenetic changes were involved in both direct and indirect radiation effects [151]. Ilnytskyy and Kovalchuk [228] recently reviewed the role of DNA methylation and small RNAs in directly irradiated and bystander tissues and in radiation-induced transgenerational effects.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As explained in the text, the sex-specific bystander effect that was reported by Koturbash et al [39,143] was observed together with DNA methylation changes. Studies have also shown that epigenetic changes were involved in both direct and indirect radiation effects [151]. Ilnytskyy and Kovalchuk [228] recently reviewed the role of DNA methylation and small RNAs in directly irradiated and bystander tissues and in radiation-induced transgenerational effects.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…In contrast, the sex-specific bystander effect that was reported by Koturbash et al [39,143] was observed together with DNA methylation changes, which is an important epigenetic phenomenon that is involved in the regulation of gene expression and genome stability. In fact, evidence indicated that epigenetic changes were involved in both direct and indirect radiation effects [151]. Until now, few studies on epigenetic changes that were involved in the in vivo bystander effect have been performed.…”
Section: In Vivo Studies On Ribe Using Animal Modelsmentioning
confidence: 99%
“…Extraordinary differences on longevity and reaching retirement on good health occur even in rich countries (70% chance in affluent areas but half that at the opposite end of the wealth spectrum and not due to poor adult habits as the death rate at aged 8 is 10fold higher for the poor. These can be compared to 18th C statistics on elite enslaved workers with life expectancies of 60 years working domestically (and having access to leftovers) often lighter skimmed and field workers of 40 years; disadvantages that get passed down generations [48] Nicotinamide and methylation pathways are important epigenetic pathways and pellagra often appeared to be familial and transgenerational as well as linked to infection and relative energy [114][115][116][117]. This switch from infection to allergy and auto-immune disease was first seen in rich white well-fed communities.…”
Section: Intergenerational Warfarementioning
confidence: 99%
“…The relationship between epigenetics and IR was comprehensively reviewed [79,80,81]. Accumulating evidence has demonstrated that IR exposures can lead to epigenetic alterations, which play an important role in genomic instability that can affect the next generations [82,83,84].…”
Section: Epigenetic Effects Of Ionizing Radiationmentioning
confidence: 99%